Copy number changes and methylation patterns in an isodicentric and a ring chromosome of 15q11-q13: report of two cases and review of literature. Issue 1 (December 2015) - Wang, Qin; Wu, Weiqing; Xu, Zhiyong; Luo, Fuwei; Zhou, Qinghua; Li, Peining; Xie, Jiansheng
Abstract Background The low copy repeats (LCRs) in chromosome 15q11-q13 have been recognized as breakpoints (BP) for not only intrachromosomal deletions and duplications but also small supernumerary marker chromosomes 15, sSMC(15)s, in the forms of isodicentric chromosome or small ring chromosome. Further characterization of copy number changes and methylation patterns in these sSMC(15)s could lead to better understanding of their phenotypic consequences. Methods Routine G-band karyotyping, fluorescence in situ hybridization (FISH), array comparative genomic hybridization (aCGH) analysis and methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) assay were performed on two Chinese patients with a sSMC(15). Results Patient 1 showed an isodicentric 15, idic(15)(q13), containing symmetrically two copies of a 7.7 Mb segment of the 15q11-q13 region by a BP3::BP3 fusion. Patient 2 showed a ring chromosome 15, r(15)(q13), with alternative one-copy and two-copy segments spanning a 12.3 Mb region. The defined methylation pattern indicated that the idic(15)(q13) and the r(15)(q13) were maternally derived. Conclusions Results from these two cases and other reported cases from literature indicated that combined karyotyping, aCGH and MS-MLPA analyses are effective to define the copy number changes and methylation patterns for sSMC(15)s in a clinical setting. The characterized genomic structure and epigenetic pattern of sSMC(15)s could lead to further gene expression profiling for better phenotype correlation.